TОWARDS THE BOOK DICTIONARY OF THE PSEUDONYMS IN 19TH CENTURY MACEDONIAN LITERATURE BY SLAVČO KOVILOSKI: (Kovilovski, Slavčo. Dictionary of the Pseudonyms in 19th Century Macedonian Literature, Sovremenost, Skopje, 2023) (Journal of Contemporary Philology, 2023)
(Kovilovski, Slavčo. Dictionary of the Pseudonyms in 19th Century Macedonian Literature, Sovremenost, Skopje, 2023)
Keywords: Review